PREDIKSI UMUR WADUK GUNUNGROWO SETELAH PENGERUKAN - Dyah Ari Wulandari (Rekayasa Sipil, 2022)
In 2015 the Gunungrowo Reservoir was dredged to reduce sedimentation. After dredging, it is necessary to carry out sedimentation analysis to determine the reservoir life to be achieved. This analysis is intended to evaluate sediment deposition patterns that have occurred up to 2015 and calculate reservoir life that can be achieved after dredging in 2015. The reservoir life is analyzed based on how long the dead storage has been filled with sediment. Sediment entering the reservoir is calculated based on reservoir bathimetri and the suspended sediment entering reservoir. The result shows most of the sediment settles in the effective storage andÂ  the reservoir life can reach up to 243 years after dredging.